2001
DOI: 10.1161/01.hyp.37.2.398
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Lithium Countertransport Activity Is Linked to Chromosome 5 in Baboons

Abstract: Abstract-The genes involved in the regulation of cellular sodium transport characteristics, which are correlated with some forms of essential hypertension, have not yet been identified. We are studying the genes and environmental factors that affect red blood cell sodium-lithium countertransport (SLC) activity and intracellular sodium (ICNa) concentration in 634 baboons that comprise 11 pedigrees of 2 and 3 generations each. A lterations in cellular sodium transport characteristics, such as red blood cell (RBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…Finally, we note that the gene loci of HsNHA1 and HsNHA2 (4q24) lie within a chromosomal region associated with hypertension in numerous linkage studies, including a sib-pair study linking SLC activity to MN blood group (4q28-q31) on chromosome 4 (36). In particular, one study in baboon mapped quantitative trait loci associated with SLC activity to chromosome 5, which is syntenic to human chromosome 4, with a maximum multipoint LOD score of 9.3 near microsatellite marker D4S1645 (37). Taken together, these findings raise the possibility that the previously uncharacterized NHA antiporters contribute to SLC activity and are candidate genes for essential hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, we note that the gene loci of HsNHA1 and HsNHA2 (4q24) lie within a chromosomal region associated with hypertension in numerous linkage studies, including a sib-pair study linking SLC activity to MN blood group (4q28-q31) on chromosome 4 (36). In particular, one study in baboon mapped quantitative trait loci associated with SLC activity to chromosome 5, which is syntenic to human chromosome 4, with a maximum multipoint LOD score of 9.3 near microsatellite marker D4S1645 (37). Taken together, these findings raise the possibility that the previously uncharacterized NHA antiporters contribute to SLC activity and are candidate genes for essential hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…Variance components linkage analysis applied to nuclear family data produced lod ¼ 2.83 on chromosome 15q at marker D15S642 16 and applied to baboon pedigrees produced lod ¼ 9.3 on chromosome 5, in the region homologous to human chromosome 4q near marker D4S1645. 17 Genome-wide association analysis of SLC in immortalized lymphoblasts identified multiple associations, many with markers near genes involved in glutathione metabolism. 18 Herein, we analyzed SLC measured twice at a 2 -3 years interval on members of 48 pedigrees.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recently, a study in a colony of 634 baboons colony localised the gene behind SLC activity to baboon chromosome 5, a homologue of human chromosome 4. 22 Genetic mapping studies of hypertension in FCH kindreds also show quantitative trait linkage of SLC activity to human chromosome 4p in the region containing a fatty acid hydrolase (CD36) and a-adducin and secondary loci at chromosome 8p near the lipoprotein lipase gene and for diastolic blood pressure chromosome 19 close to the apolipoprotein B locus. 21 Many, but not all, studies, have shown an association between a-adducin polymorphisms and hypertension in cross-sectional studies 23 and a few have implicated the fatty acid hydrolase CD 36.…”
Section: Dietary Managementmentioning
confidence: 99%